2013
DOI: 10.1097/ico.0b013e31826429bd
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Associated With the Need for Surgical Treatments in Acanthamoeba Keratitis

Abstract: Late diagnosis, low initial visual acuity, corneal neovascularization, large infiltrates, and preperforated infiltrates were associated with surgical treatment in patients presenting with AK. Surgical intervention was associated with worse visual outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…is also known for inducing a form of keratitis unresponsive to topical drugs, thus requiring a therapeutic transplant. 3,6,7,9,10 Deep anterior lamellar keratoplasty (DALK) is the surgical procedure that most suits corneal diseases affecting the stroma and sparing the endothelium. Preserving this layer provides the benefits of less risk of rejection and graft failure, when compared with PK.…”
mentioning
confidence: 99%
“…is also known for inducing a form of keratitis unresponsive to topical drugs, thus requiring a therapeutic transplant. 3,6,7,9,10 Deep anterior lamellar keratoplasty (DALK) is the surgical procedure that most suits corneal diseases affecting the stroma and sparing the endothelium. Preserving this layer provides the benefits of less risk of rejection and graft failure, when compared with PK.…”
mentioning
confidence: 99%
“…Recognition of signs and symptoms indicative of best/worst prognosis [23,24] Monotherapy with a biguanide or combined therapy using biguanides and diamidines with adjustable therapeutic regimen is effective in several cases, leading to a best outcome [4,25,27]. Ocular toxicity of current anti-Acanthamoeba drugs [4,47,48,49] Proof of efficacy of off-label drugs [50,51] or novel anti-Acanthamoeba compounds previously approved in pre-clinical trials.…”
Section: Ak Patientmentioning
confidence: 99%
“…From a series of clinical reports, identification of the signs and symptoms associated with a poor prognosis [22][23][24] is a starting point. In addition, analysis of differential therapeutic responses among individual case descriptions, retrospective or prospective epidemiological surveys and clinical trials can contribute to direct the management of disease and decide about the treatments with the greatest chance of success in different situations [2,[25][26][27].…”
Section: Reverse Translational Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies involving epidemiology, clinical course, and prognosis in ocular amoebiasis do not look into genotypes (23)(24)(25)(26). The few clinical studies that include routine genotyping of all AK cases have revealed that genotype T4 is the only cause of pathogenic AK isolated from corneal exudates or have found a single case of non-T4 genotype in their case series (11,27).…”
mentioning
confidence: 99%